Positive electrode active material, positive electrode plate as well as preparation method and application of positive electrode plate
By setting different groups on the surface of the positive electrode material with different particle sizes, directional mixing and uniform filling are achieved, the problem of poor mixing uniformity of the positive electrode active material in the prior art is solved, and the compaction density and energy density of the positive electrode sheet are improved.
Patent Information
- Application Number
- CN202410411783.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-07
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the mixing uniformity of the positive electrode active materials of different particle sizes affects the compaction density and energy efficiency of the positive electrode sheet.
Directional mixing and uniform filling are achieved by providing different groups on the surface of the positive electrode material of different particle sizes. The specific method includes mixing the first positive electrode material and the second positive electrode material, and improving its conductivity and mixing uniformity through a modifier and a carbon coating.
The compaction density and energy density of the positive electrode sheet are improved, the polarization effect is reduced, and the electrochemical performance of the battery is enhanced.
Smart Images

Figure CN119764331A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to positive electrode active materials, positive electrode sheets, and preparation methods and applications thereof. Background Art
[0002] The positive electrode active material affects the energy density, cycle performance and preparation cost of the battery, and thus affects the overall performance of the battery. In the related art, by using positive electrode active materials of different particle sizes and adjusting the ratio of positive electrode active materials of different particle sizes, the compaction density of the positive electrode sheet can be increased, and the energy density of the battery can be further improved. However, the mixing uniformity between positive electrode active materials of different particle sizes is poor, which has an adverse effect on the compaction density and energy efficiency of the positive electrode sheet. Therefore, a positive electrode active material with good mixing uniformity between different particle sizes is needed. Summary of the invention
[0003] In view of this, the present application provides a positive electrode active material, a positive electrode plate, and a preparation method and application thereof. The positive electrode active material has positive electrode materials with different particle sizes. The carbon coating layer surface of the positive electrode materials with different particle sizes has different groups, which can achieve directional mixing of positive electrode materials with different particle sizes, improve the filling uniformity of the positive electrode active material, so as to improve the compaction density and energy density of the positive electrode plate, which is conducive to the industrial application of the positive electrode active material.
[0004] In the first aspect, the present application provides a positive electrode active material, which includes a first positive electrode material and a second positive electrode material, the surface of the first positive electrode material has a first group, the surface of the second positive electrode material has a second group, the first group and the second group are independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group can be bonded and connected, and the particle size of the first positive electrode material is larger than the particle size of the second positive electrode material.
[0005] Optionally, the first group and the second group can be connected via hydrogen bonds and / or chemical bonds.
[0006] Optionally, the particle size D50 of the first positive electrode material is 0.8 μm-1.5 μm.
[0007] Optionally, the particle size D50 of the second positive electrode material is less than or equal to 0.5 μm.
[0008] Optionally, the mass ratio of the first positive electrode material to the second positive electrode material is (9-7):(3-1).
[0009] Optionally, the first positive electrode material includes a first core and a first carbon coating layer disposed on the surface of the first core, the first carbon coating layer has a first group, and in the first positive electrode material, the mass percentage of the first carbon coating layer is 1.1%-1.3%.
[0010] Optionally, the second positive electrode material includes a second inner core and a second carbon coating layer disposed on the surface of the second inner core, the second carbon coating layer has a second group, and in the second positive electrode material, the mass percentage of the second carbon coating layer is 1.1%-1.3%.
[0011] Optionally, the material of the first core and the second core is independently selected from at least one of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate and ternary materials.
[0012] The positive electrode active material provided in the present application includes positive electrode materials of different particle sizes, and the surfaces of the positive electrode materials of different particle sizes have different groups, which can achieve directional mixing and uniform filling of positive electrode materials of different particle sizes, improve the compaction density and energy density of the positive electrode sheet, and are beneficial to the application of the positive electrode material.
[0013] In a second aspect, the present application provides a method for preparing a positive electrode active material, comprising:
[0014] Mixing a first cathode material source and a first modifier to form a first mixture, and performing a first sintering to obtain a first cathode material;
[0015] Mixing a second positive electrode material source and a second modifier to form a second mixture, and performing a second sintering to obtain a second positive electrode material;
[0016] Mixing the first positive electrode material and the second positive electrode material to obtain a positive electrode active material;
[0017] The positive electrode active material includes the first positive electrode material and the second positive electrode material, the surface of the first positive electrode material has a first group, the surface of the second positive electrode material has a second group, the first group and the second group are independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group can be bonded and connected, and the particle size of the first positive electrode material is larger than the particle size of the second positive electrode material.
[0018] Optionally, the first modifier and the second modifier are independently selected from CH2CH2COOH, CH2CH2CH2COOH, NH4Cl, (NH4)2SO4, NH4NO3, Na2SO4, H2SO4, CH3C4H4O 2、 At least one of C4H4O2, NH3H2O and CH3COOH.
[0019] Optionally, the first mixture further includes a first carbon source, and the second mixture further includes a second carbon source, and the first carbon source and the second carbon source are independently selected from at least one of glucose, sucrose, citric acid, polyethylene glycol, carbon nanotubes and graphene.
[0020] Optionally, the mass ratio of the first positive electrode material source, the first modifier and the first carbon source is (2.52-2.58):(0.0038-0.0047):(6.5-6.7).
[0021] Optionally, the mass ratio of the second positive electrode material source, the second modifier and the second carbon source is (2.52-2.58):(0.0012-0.0025):(5.1-5.5).
[0022] Optionally, the temperature of the first sintering is 750° C.-800° C., and the time of the first sintering is 15 h-20 h.
[0023] Optionally, the temperature of the second sintering is 700° C.-800° C., and the time of the second sintering is 3 h-7 h.
[0024] The preparation method of the positive electrode active material provided in the present application is novel and has a simple preparation process, and can produce a positive electrode active material with high compaction density and excellent energy density.
[0025] In a third aspect, the present application provides a composite positive electrode material, the composite active material comprising a first positive electrode material and a second positive electrode material, the surface of the first positive electrode material having a first group, the surface of the second positive electrode material having a second group, the first group and the second group being independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group being connected by a connecting group, and the particle size of the first positive electrode material being larger than the particle size of the second positive electrode material.
[0026] Optionally, the first group, the connecting group and the second group are connected via hydrogen bonds and / or chemical bonds.
[0027] The connecting group in the composite positive electrode material provided in the present application can connect the first positive electrode material and the second positive electrode material, and can form a conductive network on the surface of the composite positive electrode material, resulting in an increase in the conductive pathways of the composite positive electrode material, reducing the polarization effect of the composite positive electrode material, and improving the energy efficiency of the composite positive electrode material, which is conducive to the wide application of the composite positive electrode material.
[0028] In a fourth aspect, the present application provides a positive electrode plate, which includes a positive electrode active material layer, and the positive electrode active material layer includes the positive electrode active material described in the first aspect or the positive electrode active material prepared by the preparation method described in the second aspect or the composite positive electrode material described in the third aspect.
[0029] Optionally, the compaction density of the positive electrode plate is 2.6 g / cm 3 -2.7g / cm 3 .
[0030] The positive electrode plate provided in the present application has high compaction density, small polarization, and excellent comprehensive electrochemical performance, which is conducive to the wide application of the positive electrode plate.
[0031] In a fifth aspect, the present application provides a method for preparing a positive electrode sheet, comprising:
[0032] Mixing the positive electrode active material described in the first aspect or the positive electrode active material prepared by the preparation method described in the second aspect, a directing agent and a solvent to obtain a positive electrode slurry;
[0033] The positive electrode slurry is coated and dried to obtain a positive electrode sheet.
[0034] Optionally, in the positive electrode slurry, the mass percentage of the directing agent is 1%-2%.
[0035] Optionally, the directing agent includes at least one of an iron-based polymer titanium cyanine compound, polyacetylene, polythiophene and polymerized aniline.
[0036] The present application provides a method for preparing a positive electrode sheet, which is simple, easy to operate, and has high production efficiency, and can realize large-scale production of positive electrode sheets, which is beneficial to the use of positive electrode sheets.
[0037] In a sixth aspect, the present application provides a battery, comprising a negative electrode plate and a positive electrode plate as described in the fourth aspect or a positive electrode plate prepared by the preparation method as described in the fifth aspect.
[0038] The battery provided in this application has high energy density, low preparation cost, short cycle, and excellent comprehensive electrical performance, which is conducive to improving the product competitiveness of the battery.
[0039] In a seventh aspect, the present application provides an electrical device, wherein the electrical device comprises the battery described in the sixth aspect.
[0040] The electrical equipment provided by the present application has excellent comprehensive performance, which is conducive to the wide application of the electrical equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0042] Figure 1 A schematic cross-sectional view of a positive electrode active material provided in one embodiment of the present application.
[0043] Figure 2 A flow chart of a method for preparing a positive electrode active material provided in one embodiment of the present application.
[0044] Figure 3 A schematic diagram of the internal connection method of the composite positive electrode material provided in one embodiment of the present application.
[0045] Figure 4 A schematic cross-sectional view of a positive electrode sheet provided in one embodiment of the present application.
[0046] Figure 5 A flow chart of a method for preparing a positive electrode plate provided in one embodiment of the present application. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0048] The present application provides a positive electrode active material, the positive electrode active material includes a first positive electrode material and a second positive electrode material, the surface of the first positive electrode material has a first group, the surface of the second positive electrode material has a second group, the first group and the second group are independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group can be bonded and connected, and the particle size of the first positive electrode material is larger than the particle size of the second positive electrode material. The particle size of the first positive electrode material with a large particle size and the second positive electrode material with a small particle size in the positive electrode active material provided by the present application can improve the compaction density of the positive electrode sheet; the surfaces of the first positive electrode material and the second positive electrode material have different groups, and the interaction between the first group and the second group can realize that the second positive electrode material with a small particle size is surrounded on the surface of the first positive electrode material with a large particle size, thereby realizing directional mixing and uniform filling of positive electrode materials with different particle sizes, which can avoid the problem of poor dispersibility of positive electrode materials with different particle sizes and inability to effectively improve the compaction density of the positive electrode sheet caused by directly mixing the positive electrode materials with large particle sizes and small particle sizes, and is conducive to further improving the compaction density and energy density of the positive electrode sheet. Since positive electrode active materials with large particle sizes will lead to enhanced polarization of the positive electrode sheets, resulting in a decrease in the electrochemical performance of the battery, the related art reduces the polarization effect and improves the energy efficiency by doping and coating the positive electrode active materials. At the same time, the particle size ratio of the positive electrode active materials is adjusted to increase the compaction density of the positive electrode sheets. However, it is difficult to achieve a balance between the compaction density and energy efficiency of the positive electrode sheets in actual preparation, and the preparation cycle is long, which is not conducive to the industrial application of positive electrode active materials. Positive electrode active materials with small particle sizes are prone to material loss during dressing, which is not conducive to improving processing costs, and at the same time deteriorates the performance of the battery and may also cause safety performance problems. The surfaces of the first positive electrode material and the second positive electrode material in the positive electrode active material provided in the present application have different groups, and the different groups can form a conductive network with excellent conductive properties on the surface of the positive electrode active material, which helps to improve the kinetic performance of the positive electrode sheets, reduce the positive electrode polarization effect, and improve the energy efficiency of the battery. Therefore, the positive electrode active material of the present application can achieve directional mixing of positive electrode materials with different particle sizes, improve the dynamic performance, compaction density, and energy density of the positive electrode sheet, reduce electrode polarization, and further improve battery energy efficiency.
[0049] See also Figure 1, is a cross-sectional schematic diagram of a positive electrode active material provided in one embodiment of the present application, wherein the positive electrode active material 100 includes a first positive electrode material 10 and a second positive electrode material 20, wherein the first positive electrode material 10 includes a first core 11 and a first carbon coating layer 12 disposed on the surface of the first core 11, wherein the first carbon coating layer 12 has a first group; the second positive electrode material 20 includes a second core 21 and a second carbon coating layer 22 disposed on the surface of the second core 21, wherein the second carbon coating layer 22 has a second group; the first group and the second group are independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group can be bonded and connected, and the particle size of the first positive electrode material is larger than that of the second positive electrode material. Among them, the first carbon coating layer and the second carbon coating layer can improve the stability and conductivity of the positive electrode active material.
[0050] In the present application, the first positive electrode material includes a first core, which can improve the specific capacity and cycle stability of the positive electrode active material, and is beneficial to improving the energy density of the positive electrode plate. Specifically, the material of the first core can include but is not limited to at least one of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate and ternary materials (such as nickel cobalt manganese, nickel cobalt aluminum, etc.). In one embodiment of the present application, the material of the first core can be lithium iron phosphate, which can improve the structural stability of the positive electrode active material and reduce the preparation cost and cost per kilowatt-hour of the positive electrode plate. In another embodiment of the present application, the material of the first core can be lithium cobalt oxide.
[0051] In the present application, a first group is provided on the surface of the first positive electrode material, and the first group can be connected to the second group to achieve directional mixing of the first positive electrode material and the second positive electrode material, promote uniform filling of the positive electrode active material, and improve the compaction density of the positive electrode sheet; at the same time, a conductive network can be formed on the surface of the positive electrode active material, increase the conductive path, improve the conductivity and kinetic properties of the positive electrode active material, reduce the polarization of the positive electrode sheet, and improve the electrochemical performance of the battery. Specifically, the first group can be but is not limited to at least one of -NH2, -C4H4O2, -COOH and -S. In one embodiment of the present application, the first group can be -NH2. In another embodiment of the present application, the first group can be -C4H4O2.
[0052] In one embodiment of the present application, a first carbon coating layer is provided on the surface of the first inner core, and the first carbon coating layer can improve the conductivity of the positive electrode active material, enhance the electron transport capability, and provide a connection site for the first group. In one embodiment of the present application, in the first positive electrode material, the mass percentage of the first carbon coating layer is 1.1%-1.3%, so that the structural stability of the first positive electrode material can be improved. Specifically, in the first positive electrode material, the mass percentage of the first carbon coating layer can be 1.12%, 1.14%, 1.15%, 1.18%, 1.2%, 1.22%, 1.25%, 1.28% or 1.3%, etc. In one embodiment of the present application, in the first positive electrode material, the mass percentage of the first carbon coating layer can be 1.1%-1.22%. In another embodiment of the present application, in the first positive electrode material, the mass percentage of the first carbon coating layer can be 1.2%-1.3%.
[0053] In one embodiment of the present application, a first group is provided on the surface of the first carbon coating layer, and the first group can be connected to the second group to achieve directional mixing of the first positive electrode material and the second positive electrode material, promote uniform filling of the positive electrode active material, and improve the compaction density of the positive electrode plate; at the same time, a conductive network can be formed on the surface of the positive electrode active material, increase the conductive path, improve the conductivity and kinetic properties of the positive electrode active material, reduce the polarization of the positive electrode plate, and improve the electrochemical performance of the battery. Specifically, the first group can be but is not limited to at least one of -NH2, -C4H4O2, -COOH and -S. In one embodiment of the present application, the first group can be -NH2. In another embodiment of the present application, the first group can be -C4H4O2.
[0054] In one embodiment of the present application, in the first cathode material, the mass percentage of the first group is 1.1%-1.3%. Specifically, in the first cathode material, the mass percentage of the first group can be 1.12%, 1.14%, 1.15%, 1.18%, 1.2%, 1.22%, 1.25%, 1.28% or 1.3%, etc. In one embodiment of the present application, in the first cathode material, the mass percentage of the first group can be 1.1%-1.22%. In another embodiment of the present application, in the first cathode material, the mass percentage of the first group can be 1.2%-1.3%.
[0055] In one embodiment of the present application, the particle size D50 of the first positive electrode material is 0.8μm-1.5μm. The first positive electrode material with a larger particle size can increase the tap density of the positive electrode active material, and further increase the compaction density and energy density of the positive electrode sheet. Specifically, the particle size D50 of the first positive electrode material may be, but is not limited to, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm or 1.5μm, etc. In one embodiment of the present application, the particle size D50 of the first positive electrode material may be 0.8μm-1.1μm. In another embodiment of the present application, the particle size D50 of the first positive electrode material may be 1μm-1.5μm.
[0056] In one embodiment of the present application, in the positive electrode active material, the mass percentage of the first positive electrode material is 70%-90%, so that the tap density of the positive electrode active material can be increased, and the compaction density and energy density of the positive electrode sheet can be further increased. Specifically, the mass percentage of the first positive electrode material can be 70%, 75%, 78%, 80%, 84%, 88% or 90%, etc. In one embodiment of the present application, the mass percentage of the first positive electrode material can be 70%-83%. In another embodiment of the present application, the mass percentage of the first positive electrode material can be 75%-90%.
[0057] In the present application, the second positive electrode material includes a second core, and the second core can improve the specific capacity and cycle stability of the positive electrode active material, which is beneficial to improve the energy density of the positive electrode plate. Specifically, the material of the second core can include but is not limited to at least one of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate and ternary materials (such as nickel cobalt manganese, nickel cobalt aluminum, etc.). In one embodiment of the present application, the material of the second core can be lithium iron phosphate, which can improve the structural stability of the positive electrode active material and reduce the preparation cost and cost per kilowatt-hour of the positive electrode plate. In another embodiment of the present application, the material of the second core can be lithium cobalt oxide. In some embodiments, the material of the first core is the same as that of the second core, which can further improve the stability and conductivity of the positive electrode active material, improve the energy density of the positive electrode plate, and further improve the energy efficiency of the battery.
[0058] In one embodiment of the present application, a second carbon coating layer is disposed on the surface of the second inner core. The second carbon coating layer can improve the conductivity of the positive electrode active material, enhance the electron transport capability, and provide a connection site for the second group.
[0059] In one embodiment of the present application, in the second positive electrode material, the mass percentage of the second carbon coating layer is 1.1%-1.3%, so that the structural stability of the second positive electrode material can be improved. Specifically, in the second positive electrode material, the mass percentage of the second carbon coating layer can be 1.12%, 1.14%, 1.15%, 1.18%, 1.2%, 1.22%, 1.25%, 1.28% or 1.3%, etc. In one embodiment of the present application, in the second positive electrode material, the mass percentage of the second carbon coating layer can be 1.1%-1.22%. In another embodiment of the present application, in the second positive electrode material, the mass percentage of the second carbon coating layer can be 1.2%-1.3%.
[0060] In one embodiment of the present application, a second group is provided on the surface of the second carbon coating layer, and the second group can be connected to the first group to achieve directional mixing of the first positive electrode material and the second positive electrode material, promote uniform filling of the positive electrode active material, and improve the compaction density of the positive electrode sheet; at the same time, a conductive network can be formed on the surface of the positive electrode active material, increase the conductive path, improve the conductivity and kinetic properties of the positive electrode active material, reduce the polarization of the positive electrode sheet, and improve the electrochemical performance of the battery. Specifically, the second group can be but is not limited to at least one of -NH2, -C4H4O2, -COOH and -S. In one embodiment of the present application, the second group can be -COOH. In another embodiment of the present application, the second group can be -S.
[0061] In one embodiment of the present application, in the second cathode material, the mass percentage of the second group is 1.1%-1.3%. Specifically, in the second cathode material, the mass percentage of the second group can be 1.12%, 1.14%, 1.15%, 1.18%, 1.2%, 1.22%, 1.25%, 1.28% or 1.3%, etc. In one embodiment of the present application, in the second cathode material, the mass percentage of the second group can be 1.1%-1.22%. In another embodiment of the present application, in the second cathode material, the mass percentage of the second group can be 1.2%-1.3%.
[0062] In one embodiment of the present application, the first group and the second group can be bonded and connected, and the first group and the second group are easy to form a conductive network, increase the conductive path, reduce the polarization effect, and improve the electrochemical performance of the battery. Specifically, the second group can be, but is not limited to, at least one of -NH2, -C4H4O2, -COOH and -S. In one embodiment of the present application, the first group is -NH2 or -C4H4O2, and the second group can be -COOH or -S.
[0063] In one embodiment of the present application, the particle size D50 of the second positive electrode material is less than or equal to 0.5 μm, and the second positive electrode material with a smaller particle size can be filled between the first positive electrode material to promote the uniform filling of the positive electrode active material, and further improve the compaction density and energy density of the positive electrode sheet. Specifically, the particle size D50 of the second positive electrode material may be, but is not limited to, less than or equal to 0.5 μm, less than or equal to 0.4 μm, less than or equal to 0.3 μm, less than or equal to 0.2 μm, less than or equal to 0.15 μm, or less than or equal to 0.1 μm, etc. In one embodiment of the present application, the particle size D50 of the second positive electrode material may be less than or equal to 0.25 μm. In another embodiment of the present application, the particle size D50 of the second positive electrode material may be less than or equal to 0.1 μm.
[0064] In one embodiment of the present application, the particle size D50 of the first positive electrode material is 0.8μm-1.5μm, and the particle size D50 of the second positive electrode material is less than or equal to 0.3μm, which can further promote the uniform mixing of the positive electrode active material and improve the compaction density and energy density of the positive electrode sheet. Specifically, the particle size D50 of the first positive electrode material can be, but is not limited to, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm or 1.5μm, etc.; the particle size D50 of the second positive electrode material can be, but is not limited to, less than or equal to 0.3μm, less than or equal to 0.28μm, less than or equal to 0.25μm, less than or equal to 0.2μm, less than or equal to 0.15μm, or less than or equal to 0.1μm, etc. In one embodiment of the present application, the particle size D50 of the first positive electrode material is 0.8 μm-1.5 μm, and the particle size D50 of the second positive electrode material is less than or equal to 0.3 μm.
[0065] The above D50 is the particle size corresponding to when the cumulative particle size distribution volume percentage reaches 50%. The physical meaning is that the volume of particles with a particle size greater than the particle size D50 accounts for 50%, and the volume of particles with a particle size less than the particle size D50 also accounts for 50%. D50 is also called the median diameter or median particle size.
[0066] When measuring the particle size D50 of the first positive electrode material and / or the second positive electrode material, the test method specifically includes the following steps: a) disassembling a completely discharged battery to obtain a positive electrode sheet, and then cutting any position of the dressing area by argon ions to obtain a cross-sectional sample of the positive electrode sheet; b) placing the above-mentioned positive electrode sheet cross-sectional sample in a SEM for observation, adjusting the electron microscope voltage and magnification according to actual needs to ensure that enough particles in the above-mentioned sample can be clearly seen and photographed to obtain a SEM photo; c) the obtained SEM photo can be imported into a grayscale debugging software (such as Geodict) to count the particle size of the particles, or the particle size of the particles can be directly counted by manual naked eye identification; d) 20-30 experiments are cumulatively performed, and the number of particles counted in each experiment is not less than 500 pcs. After counting the above results, the particle size D50 of the first positive electrode material and / or the second positive electrode material in the positive electrode sheet is obtained.
[0067] In one embodiment of the present application, in the positive electrode active material, the mass percentage of the second positive electrode material is 10%-30%, so that the compaction density and energy density of the positive electrode active material can be improved. Specifically, the mass percentage of the second positive electrode material can be 10%, 15%, 18%, 20%, 24%, 28% or 30%, etc. In one embodiment of the present application, the mass percentage of the second positive electrode material can be 10%-25%. In another embodiment of the present application, the mass percentage of the second positive electrode material can be 15%-30%.
[0068] The positive electrode active material in the present application may include a plurality of first positive electrode materials and a plurality of second positive electrode materials. In one embodiment of the present application, the mass ratio of the first positive electrode material to the second positive electrode material is (9-7): (3-1), and the mass ratio of the first positive electrode material is high, which can improve the compaction density of the positive electrode sheet. Specifically, the mass ratio of the first positive electrode material to the second positive electrode material may be, but is not limited to, 9:3, 9:1.5, 9:1, 8:1, 8:1.5, 8:3, 7:1, 7:1.5 or 7:3, etc. In one embodiment of the present application, the mass ratio of the first positive electrode material to the second positive electrode material may be (8-7): (2.5-1). In another embodiment of the present application, the mass ratio of the first positive electrode material to the second positive electrode material may be (9-8): (3-2).
[0069] In one embodiment of the present application, the tap density of the positive electrode active material is 0.8 g / cm 3 -1.0g / cm 3 This can increase the compaction density of the positive electrode active material, thereby increasing the energy density of the positive electrode sheet. Specifically, the tap density of the positive electrode active material can be, but is not limited to, 0.8 g / cm 3 , 0.82g / cm 3 、0.84g / cm3 , 0.86g / cm 3 , 0.88g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 、0.98g / cm 3 or 1.0g / cm 3 In one embodiment of the present application, the tap density of the positive electrode active material may be 0.8 g / cm 3 -0.89g / cm 3 In another embodiment of the present application, the tap density of the positive electrode active material can be 0.86 g / cm 3 -1.0g / cm 3 .
[0070] See also Figure 2 , is a flow chart of a method for preparing a positive electrode active material provided in one embodiment of the present application, comprising:
[0071] S101: mixing a first positive electrode material source and a first modifier to form a first mixture, and obtaining a first positive electrode material after a first sintering;
[0072] S102: mixing a second positive electrode material source and a second modifier to form a second mixture, and performing a second sintering to obtain a second positive electrode material;
[0073] S103: Mix the first positive electrode material and the second positive electrode material to obtain a positive electrode active material.
[0074] The preparation method provided in the present application is novel and has a simple preparation process. It can produce positive electrode active materials with different particle size ratios. The positive electrode materials with different particle sizes have different groups on their surfaces, which can achieve directional mixing and uniform filling of positive electrode materials with different particle sizes, thereby improving the compaction density and energy density of the positive electrode sheet. The positive electrode active material described in any of the above embodiments can be produced by the preparation method.
[0075] In the present application, the first positive electrode material source is used to form the first core, and the selection of the first positive electrode material source is related to the material of the first core, and the first positive electrode material source includes all the metal elements in the material of the first core. Specifically, the first positive electrode material source may include but is not limited to at least one of a lithium source, a phosphorus source, an iron source, a cobalt source, a nickel source, a manganese source, and an aluminum source. In one embodiment of the present application, when the material of the first core is lithium iron phosphate, the first positive electrode material source includes a lithium source, an iron source, and a phosphorus source. In another embodiment of the present application, when the material of the first core is lithium cobalt oxide, the first positive electrode material source includes a lithium source and a cobalt source. Specifically, the lithium source may include but is not limited to at least one of Li2CO3, LiOH, CH3COOLi, Li3PO4, and Li2SO4; the iron source may include but is not limited to at least one of FeSO4, FeC2O4, FeCl3, Fe2O3, and Fe3O4; the phosphorus source may include but is not limited to at least one of H3PO4, NH4H2PO4, (NH4)2HPO4, Na2HPO4, and NaH2PO4. In one embodiment of the present application, the lithium source may be Li2CO3, the iron source may be Fe2O3, and the phosphorus source may be NH4H2PO4. In another embodiment of the present application, the lithium source may be LiOH, the iron source may be FeC2O4, and the phosphorus source may be NaH2PO4.
[0076] In one embodiment of the present application, when the first cathode material source includes a phosphorus source, a lithium source and an iron source, the mass ratio of the phosphorus source, the lithium source and the iron source is (0.52-0.58): 1: 1, so that a cathode active material with excellent conductive properties can be obtained. Specifically, the mass ratio of the phosphorus source, the lithium source and the iron source can be, but is not limited to, 0.52: 1: 1, 0.53: 1: 1, 0.54: 1: 1, 0.55: 1: 1, 0.56: 1: 1, 0.57: 1: 1 or 0.58: 1: 1, etc. In one embodiment of the present application, the mass ratio of the phosphorus source, the lithium source and the iron source can be (0.52-0.55): 1: 1. In another embodiment of the present application, the mass ratio of the phosphorus source, the lithium source and the iron source is (0.54-0.58): 1: 1.
[0077] In the present application, the first modifier grafts the first group on the surface of the first positive electrode material to improve the conductivity of the positive electrode active material, promote the uniformity of the positive electrode active material, increase the compaction density of the positive electrode sheet, and reduce the polarization of the positive electrode sheet. Specifically, the corresponding first modifier can be selected according to the required first group. Exemplary, the first modifier can include but is not limited to NH4Cl, (NH4)2SO4, NH4NO3, CH3C4H4O 2、At least one of C4H4O2, NH3H2O, CH2CH2COOH, CH2CH2CH2COOH, Na2SO4, H2SO4 and CH3COOH, and the corresponding modification group is at least one of -NH2, -C4H4O2, -COOH and -S. In one embodiment of the present application, the first modifier may be NH4Cl, in which case the first group is -NH2. In another embodiment of the present application, the first modifier may be C4H4O2, in which case the first group is -C4H4O2. In some embodiments, the first modifier may be a first carbon layer modifier, so that the first group is grafted onto the surface of the first carbon coating layer, which may further improve the conductivity of the positive electrode active material.
[0078] In one embodiment of the present application, the first mixture also includes a first carbon source, and the first carbon source is used to form a first carbon coating layer to improve the conductivity of the positive electrode active material. In one embodiment of the present application, the first carbon source includes at least one of an organic carbon source and an inorganic carbon source. Specifically, the first carbon source may include but is not limited to at least one of glucose, sucrose, citric acid, polyethylene glycol, carbon nanotubes and graphene. In one embodiment of the present application, the first carbon source may be glucose and sucrose. In another embodiment of the present application, the first carbon source may be a carbon nanotube.
[0079] In one embodiment of the present application, the mass ratio of the first positive electrode material source, the first modifier and the first carbon source is (2.52-2.58): (0.0038-0.0047): (6.5-6.7), so that the positive electrode sheet can have both high compaction density and energy efficiency. Specifically, the mass ratio of the first positive electrode material source, the first modifier and the first carbon source can be, but is not limited to, 2.52: 0.0038: 6.5, 2.53: 0.004: 6.55, 2.54: 0.0042: 6.58, 2.55: 0.0044: 6.6, 2.56: 0.0045: 6.65, 2.57: 0.0047: 6.7 or 2.58: 0.0047: 6.7, etc. In one embodiment of the present application, the mass ratio of the first cathode material source, the first modifier, and the first carbon source may be (2.52-2.54):(0.0038-0.0042):(6.5-6.68). In another embodiment of the present application, the mass ratio of the first cathode material source, the first modifier, and the first carbon source may be (2.54-2.58):(0.004-0.0047):(6.65-6.7).
[0080] In one embodiment of the present application, the first mixture also includes a first doping modifier. The first doping modifier can dope and modify the first cathode material source to improve the conductivity of the cathode active material. At the same time, the first doping modifier can affect the unit cell parameters and can regulate the particle size of the first cathode material, which is beneficial to reduce the battery impedance. Specifically, the first doping modifier can be but is not limited to at least one of tetrabutyl titanate, TiO2, V2O5, MgCl2, MgSO4 and MnSO4. In one embodiment of the present application, the first doping modifier can be TiO2. In another embodiment of the present application, the first doping modifier can be MgCl2.
[0081] In one embodiment of the present application, the mass ratio of the first positive electrode material source, the first modifier, the first doping modifier and the first carbon source is (2.52-2.58):(0.0038-0.0047):(0.0001-0.0005):(6.5-6.7). Specifically, the mass ratio of the first positive electrode material source, the first modifier, the first doping modifier and the first carbon source can be, but is not limited to, 2.52:0.0038:0.0001:6.5, 2.53:0.004:0.0002:6.55, 2.54:0.0042:0.00025:6.58, 2.55:0.0044:0.0003:6.6, 2.56:0.0045:0.00035:6.65, 2.57:0.0047:0.0004:6.7 or 2.58:0.0047:0.0005:6.7, etc. In one embodiment of the present application, the mass ratio of the first cathode material source, the first modifier, the first doping modifier and the first carbon source can be (2.52-2.55): (0.0038-0.0042): (0.0001-0.00032): (6.5-6.63). In another embodiment of the present application, the mass ratio of the first cathode material source, the first modifier, the first doping modifier and the first carbon source can be (2.54-2.58): (0.0041-0.0047): (0.0003-0.0005): (6.6-6.7).
[0082] In one embodiment of the present application, the temperature of the first sintering is 750°C-800°C. Specifically, the temperature of the first sintering may be, but is not limited to, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C. In one embodiment of the present application, the temperature of the first sintering may be 750°C-770°C. In another embodiment of the present application, the temperature of the first sintering may be 760°C-800°C.
[0083] In one embodiment of the present application, the first sintering time is 15h-20h. Specifically, the first sintering time may be, but is not limited to, 15h, 16h, 16.5h, 17h, 18h, 19h or 20h. In one embodiment of the present application, the first sintering time may be 15h-18h. In another embodiment of the present application, the first sintering time may be 16h-20h.
[0084] In one embodiment of the present application, the first cathode material source, the first modifier and the first carbon source are mixed and stirred, and then the first sintering is performed. Specifically, the stirring time may be, but is not limited to, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 9 hours or 10 hours. In one embodiment of the present application, the stirring time may be 6 hours to 8 hours. In another embodiment of the present application, the stirring time may be 7 hours to 10 hours.
[0085] In one embodiment of the present application, the preparation method of the first positive electrode material may include but is not limited to at least one of a solid phase method, a liquid phase method, a sol-gel method and a spray drying method. In one embodiment of the present application, the preparation method of the first positive electrode material is a solid phase method, which can obtain a first positive electrode material with a larger particle size, which is beneficial to improve the compaction density and energy density of the positive electrode active material. Exemplarily, the first positive electrode material source, the first modifier and the first carbon source are added to the first solvent, mixed, stirred, and ground to form a first mixture, and the first solvent is removed by spray drying, and a first sintering is performed to obtain the first positive electrode material. In some embodiments, the first solvent can be an aqueous solution.
[0086] In the present application, the second positive electrode material source is used to form the second core, and the selection of the second positive electrode material source is related to the material of the second core, and the second positive electrode material source includes all the metal elements in the material of the second core. Specifically, the second positive electrode material source may include but is not limited to at least one of a lithium source, a phosphorus source, an iron source, a cobalt source, a nickel source, a manganese source and an aluminum source. In one embodiment of the present application, when the material of the second core is lithium iron phosphate, the second positive electrode material source includes a lithium source, an iron source and a phosphorus source. In another embodiment of the present application, when the material of the second core is lithium cobaltate, the second positive electrode material source includes a lithium source and a cobalt source.
[0087] In one embodiment of the present application, when the second cathode material source includes a phosphorus source, a lithium source and an iron source, the mass ratio of the phosphorus source, the lithium source and the iron source is (0.52-0.58): 1: 1. Specifically, the mass ratio of the phosphorus source, the lithium source and the iron source may be, but is not limited to, 0.52: 1: 1, 0.53: 1: 1, 0.54: 1: 1, 0.55: 1: 1, 0.56: 1: 1, 0.57: 1: 1 or 0.58: 1: 1, etc. In one embodiment of the present application, the mass ratio of the phosphorus source, the lithium source and the iron source may be (0.52-0.55): 1: 1. In another embodiment of the present application, the mass ratio of the phosphorus source, the lithium source and the iron source is (0.54-0.58): 1: 1.
[0088] In the present application, the second modifier grafts the second group on the surface of the second carbon coating layer to improve the conductivity of the positive electrode active material, promote the uniformity of the positive electrode active material, increase the compaction density of the positive electrode sheet, and reduce the polarization of the positive electrode sheet. Since the first group and the second group cannot be the same, the same groups cannot form a conductive polymer and cannot form a conductive network, resulting in an enhanced polarization of the positive electrode active material and a decreased energy efficiency of the battery. In other words, the second modifier cannot be the same as the first modifier. When the first modifier is NH4Cl, (NH4)2SO4, NH4NO3, CH3C4H4O 2、 C4H4O2, NH3H2O, etc., and the second modifier is selected from CH2CH2COOH, CH2CH2CH2COOH, Na2SO4, H2SO4, CH3COOH, etc. Specifically, the corresponding second modifier can be selected according to the required second group. Exemplary, the second modifier can include but is not limited to NH4Cl, (NH4)2SO4, NH4NO3, CH3C4H4O 2、 At least one of C4H4O2, NH3H2O, CH2CH2COOH, CH2CH2CH2COOH, Na2SO4, H2SO4 and CH3COOH. In one embodiment of the present application, the second modifier may be CH2CH2COOH, in which case the second group is -COOH. In another embodiment of the present application, the second modifier may be Na2SO4, in which case the second group is -S. In some embodiments, the second modifier may be a second carbon layer modifier, so that the second group is grafted onto the surface of the second carbon coating layer, which may further improve the conductivity of the positive electrode active material.
[0089] In the present application, the second carbon source is used to form a second carbon coating layer to improve the conductivity of the positive electrode active material. In one embodiment of the present application, the second carbon source includes at least one of an organic carbon source and an inorganic carbon source. Specifically, the second carbon source may include but is not limited to at least one of glucose, sucrose, citric acid, polyethylene glycol, carbon nanotubes and graphene. In one embodiment of the present application, the second carbon source may be glucose. In another embodiment of the present application, the second carbon source may be a carbon nanotube.
[0090] In one embodiment of the present application, the mass ratio of the second positive electrode material source, the second modifier and the second carbon source is (2.52-2.58): (0.0012-0.0025): (5.1-5.5), so that the positive electrode sheet can have both high compaction density and energy efficiency. Specifically, the mass ratio of the second positive electrode material source, the second modifier and the second carbon source can be, but is not limited to, 2.52: 0.0012: 5.1, 2.53: 0.0015: 5.15, 2.54: 0.0016: 5.2, 2.55: 0.0018: 5.3, 2.56: 0.002: 5.4, 2.57: 0.0022: 5.45 or 2.58: 0.0025: 5.5, etc. In one embodiment of the present application, the mass ratio of the second cathode material source, the second modifier, and the second carbon source may be (2.52-2.54):(0.0012-0.0019):(5.1-5.4). In another embodiment of the present application, the mass ratio of the second cathode material source, the second modifier, and the second carbon source may be (2.54-2.58):(0.0018-0.0025):(5.2-5.5).
[0091] In one embodiment of the present application, the second mixture also includes a second doping modifier, which can be used to dope and modify the second core to improve the conductivity of the positive electrode active material; the particle size of the second positive electrode material can be regulated by changing the unit cell parameters to reduce the battery impedance. Specifically, the second doping modifier can be, but is not limited to, at least one of tetrabutyl titanate, TiO2, V2O5, MgCl2, MgSO4 and MnSO4. In one embodiment of the present application, the second doping modifier can be TiO2. In another embodiment of the present application, the second doping modifier can be MgCl2.
[0092] In one embodiment of the present application, the mass ratio of the second positive electrode material source, the second modifier, the second doping modifier and the second carbon source is (2.52-2.58):(0.0012-0.0025):(0.0001-0.0005):(5.1-5.5). Specifically, the mass ratio of the second positive electrode material source, the second modifier, the second doping modifier and the second carbon source can be, but is not limited to, 2.52:0.0012:0.0001:5.1, 2.53:0.0015:0.0002:5.15, 2.54:0.0018:0.00025:5.2, 2.55:0.0019:0.0003:5.25, 2.56:0.002:0.00035:5.3, 2.57:0.0023:0.0004:5.4 or 2.58:0.0025:0.0005:5.5, etc. In one embodiment of the present application, the mass ratio of the second cathode material source, the second modifier, the second doping modifier and the second carbon source can be (2.52-2.55): (0.0012-0.0017): (0.0001-0.00032): (5.1-5.3). In another embodiment of the present application, the mass ratio of the second cathode material source, the second modifier, the second doping modifier and the second carbon source can be (2.54-2.58): (0.0015-0.0025): (0.0003-0.0005): (5.25-5.5).
[0093] In one embodiment of the present application, the preparation method of the second positive electrode material may include but is not limited to at least one of a solid phase method, a liquid phase method, a sol-gel method and a spray drying method. In one embodiment of the present application, the preparation method of the second positive electrode material is a liquid phase method, which can obtain a second positive electrode material with a smaller particle size, which is beneficial to improve the filling degree and compaction density of the positive electrode active material. Exemplarily, the second positive electrode material source, the second modifier and the second carbon source are added to the second solvent and mixed, and after heat treatment, washed and dried, and a second sintering is performed to obtain the second positive electrode material. In some embodiments, the second solvent can be an aqueous solution.
[0094] In one embodiment of the present application, the temperature of the second sintering is 700°C-800°C. Specifically, the temperature of the second sintering may be, but is not limited to, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C. In one embodiment of the present application, the temperature of the second sintering may be 700°C-770°C. In another embodiment of the present application, the temperature of the second sintering may be 730°C-800°C.
[0095] In one embodiment of the present application, the second sintering time is 3h-7h. Specifically, the second sintering time may be, but is not limited to, 3h, 3.5h, 4h, 4.5h, 5h, 6h or 7h. In one embodiment of the present application, the second sintering time may be 3h-5.5h. In another embodiment of the present application, the second sintering time may be 4h-7h.
[0096] In one embodiment of the present application, heat treatment is also included before the second sintering, and the temperature of the heat treatment is 100°C-200°C, and the time of the heat treatment is 8h-12h, which can promote the synthesis of the second positive electrode material. Specifically, the temperature of the heat treatment may be, but not limited to, 100°C, 120°C, 140°C, 160°C, 180°C, 190°C or 200°C, etc.; the time of the heat treatment may be, but not limited to, 8h, 9h, 10h, 10.5h, 11h, 11.5h or 12h, etc. In one embodiment of the present application, the temperature of the heat treatment may be 100°C-180°C, and the time of the heat treatment may be 8h-9h. In another embodiment of the present application, the temperature of the heat treatment may be 150°C-200°C, and the time of the heat treatment may be 9h-12h.
[0097] The present application also provides a composite positive electrode material, including a first positive electrode material and a second positive electrode material, the first positive electrode material surface has a first group, the second positive electrode material surface has a second group, the first group and the second group are independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group are connected by a connecting group, and the particle size of the first positive electrode material is larger than the particle size of the second positive electrode material. In the composite positive electrode material provided by the present application, the connecting group can connect the first group and the second group to form a conductive network on the surface of the composite positive electrode material, increase the number of conductive paths of the composite positive electrode material, reduce the polarization effect of the composite positive electrode material, and improve the electrochemical performance of the composite positive electrode material; the different groups on the surface of the first positive electrode material and the second positive electrode material with different particle sizes can realize the directional mixing of the composite positive electrode material, improve the compaction density and energy density of the positive electrode sheet, and facilitate the wide application of the composite positive electrode material.
[0098] In one embodiment of the present application, the linking group includes but is not limited to at least one of -CONH- and -C4H4O2S-. The linking group is formed by the first group and the second group. For example, the -CONH- bond is formed by the dehydration of -NH2 and -COOH, and -C4H4O2S- is formed by the bonding of -C4H4O2 and -S.
[0099] See also Figure 3, is a schematic diagram of the connection method inside the composite positive electrode material provided in one embodiment of the present application, in which the first group 13 on the surface of the first positive electrode material 10 is connected to the second group 23 on the surface of the second positive electrode material 20 through a connecting group 30, so that the second positive electrode material can be arranged around the first positive electrode material, and the directional mixing of the composite positive electrode material is achieved to form a conductive compound containing conjugated functional groups with electronic conductivity such as -CONH- and -C4H4O2S-, thereby forming a conductive network, increasing the number of conductive paths of the composite positive electrode material, and improving the compaction density and energy density of the positive electrode sheet.
[0100] In the present application, the composite positive electrode material may include a plurality of first positive electrode materials and a plurality of second positive electrode materials, wherein the plurality of second positive electrode materials are arranged around a first positive electrode material. In one embodiment of the present application, the composite positive electrode material includes a plurality of composite particles, wherein the composite particles include a first positive electrode material and a plurality of second positive electrode materials arranged around the first positive electrode material.
[0101] In one embodiment of the present application, the composite positive electrode material further includes a directing agent. The connecting group is derived from the directing agent and can be connected with the first group and the second group to form a conductive network. The directing agent that does not form a conductive network with the first group and the second group still exists in the composite positive electrode material in the form of a directing agent.
[0102] In one embodiment of the present application, a method for preparing a composite positive electrode material comprises: mixing a first positive electrode material, a second positive electrode material and a directing agent to obtain a composite positive electrode material. The preparation method provided by the present application is novel, has a simple process, and can produce a composite positive electrode material with high energy density and good electrical conductivity. The composite positive electrode material described in any of the above embodiments can be obtained by the preparation method.
[0103] In one embodiment of the present application, the reaction temperature of the composite positive electrode material is 80°C-100°C, and the reaction time is 1h-2h. In this way, a composite positive electrode material with high energy density and excellent conductivity can be obtained. Specifically, the reaction temperature of the composite positive electrode material may be, but not limited to, 80°C, 85°C, 88°C, 90°C, 92°C, 95°C or 100°C, etc.; the reaction time may be, but not limited to, 1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h. In one embodiment of the present application, the reaction temperature of the composite positive electrode material may be 80°C-92°C, and the reaction time may be 1h-1.6h. In another embodiment of the present application, the reaction temperature of the composite positive electrode material may be 90°C-100°C, and the reaction time may be 1.5h-2h.
[0104] In one embodiment of the present application, the mass ratio of the first positive electrode material, the second positive electrode material and the guiding agent is (70-90): (10-30): (1-2). Specifically, the mass ratio of the first positive electrode material, the second positive electrode material and the guiding agent may be, but is not limited to, 70:10:1, 72:12:1.2, 78:15:1.3, 80:18:1.4, 82:20:1.6, 86:22:1.7 or 90:30:1, etc. In one embodiment of the present application, the mass ratio of the first positive electrode material, the second positive electrode material and the guiding agent may be (70-83): (10-25): (1-1.7). In another embodiment of the present application, the mass ratio of the first positive electrode material, the second positive electrode material and the guiding agent may be (80-90): (20-30): (1.6-2).
[0105] The present application also provides a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer includes the positive electrode active material described in any one of the above embodiments. Figure 4 , is a cross-sectional schematic diagram of a positive electrode sheet provided in one embodiment of the present application, wherein the positive electrode sheet 200 includes a positive electrode current collector 40 and a positive electrode active material layer 50 disposed on the surface of the positive electrode current collector 40. The positive electrode sheet provided in the present application has a positive electrode active material with good filling effect and excellent conductive performance, thereby improving the compaction density and energy density of the positive electrode sheet.
[0106] In one embodiment of the present application, the positive electrode active material layer further includes a positive electrode conductive agent, which can increase the conductivity of the positive electrode active material and improve the electronic conductivity. Specifically, the positive electrode conductive agent may include, but is not limited to, at least one of carbon nanotubes, conductive carbon black, small particle conductive carbon black, graphite, acetylene black and graphene. In one embodiment of the present application, the positive electrode conductive agent may be graphite. In another embodiment of the present application, the positive electrode conductive agent may be conductive carbon black.
[0107] In one embodiment of the present application, the mass percentage of the conductive agent is 1.5%-1.8%, so that the conductivity of the positive electrode plate can be improved. Specifically, the mass percentage of the conductive agent can be, but is not limited to, 1.5%, 1.55%, 1.58%, 1.6%, 1.62%, 1.65%, 1.7%, 1.75%, 1.78% or 1.8%, etc. In one embodiment of the present application, the mass percentage of the conductive agent can be 1.5%-1.68%. In another embodiment of the present application, the mass percentage of the conductive agent can be 1.61%-1.8%.
[0108] In one embodiment of the present application, the positive electrode active material layer also includes a positive electrode binder, which can improve the binding ability of the components in the positive electrode active material layer and improve the binding ability between the positive electrode active material layer and the current collector. Specifically, the positive electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the positive electrode binder can be polyvinylidene fluoride. In another embodiment of the present application, the positive electrode binder can be sodium carboxymethyl cellulose.
[0109] In one embodiment of the present application, the mass percentage of the positive electrode binder is 2.5%-2.8%, so that the bonding ability of the positive electrode sheet can be improved. Specifically, the mass percentage of the positive electrode binder can be, but is not limited to, 2.5%, 2.55%, 2.58%, 2.6%, 2.62%, 2.65%, 2.7%, 2.75%, 2.78% or 2.8%, etc. In one embodiment of the present application, the mass percentage of the positive electrode binder can be 2.5%-2.65%. In another embodiment of the present application, the mass percentage of the positive electrode binder can be 2.6%-2.8%.
[0110] In one embodiment of the present application, the compaction density of the positive electrode sheet is 2.6 g / cm 3 -2.7g / cm 3 , which can reduce the polarization effect and improve the energy efficiency of the battery. Specifically, the compaction density of the positive electrode sheet can be 2.6g / cm 3 , 2.62g / cm 3 , 2.64g / cm 3 , 2.65g / cm 3 , 2.66g / cm 3 , 2.68g / cm 3 or 2.7 g / cm 3 In one embodiment of the present application, the compaction density of the positive electrode sheet can be 2.6 g / cm 3 -2.67g / cm 3 In another embodiment of the present application, the compaction density of the positive electrode sheet is 2.62 g / cm 3 -2.7g / cm 3 .
[0111] See also Figure 5 , is a flow chart of a method for preparing a positive electrode sheet provided in one embodiment of the present application, comprising:
[0112] S201: mixing the positive electrode active material, the directing agent and the solvent described in any one of the above embodiments to obtain a positive electrode slurry;
[0113] S202: The positive electrode slurry is coated and dried to obtain a positive electrode sheet.
[0114] The positive electrode sheet preparation method provided by the present application is simple, easy to operate, and has high production efficiency, and can realize large-scale production of positive electrode sheets, which is beneficial to the use of positive electrode sheets. The positive electrode sheet preparation method provided by the present application can produce the positive electrode sheet described in any of the above embodiments.
[0115] In the present application, the directing agent can promote the chemical bond connection between the first group and the second group, form a conductive network on the surface of the positive electrode active material, improve the dynamic performance of the positive electrode sheet, and reduce the polarization effect of the positive electrode sheet. The second positive electrode material in the positive electrode active material layer surrounds the first positive electrode material, and the first group and the second group on the surface of the first positive electrode material and the second positive electrode material are connected by the directing agent to form a conductive path. The conductive network formed on the surface of the positive electrode active material improves the dynamic performance of the positive electrode sheet and reduces the polarization effect of the positive electrode sheet; at the same time, the directional mixing between the first positive electrode material and the second positive electrode material is achieved, the compaction density of the positive electrode sheet is increased, and the energy density of the battery is improved.
[0116] In one embodiment of the present application, the guiding agent may include, but is not limited to, at least one of an iron-based polymer phthalocyanine compound, polyacetylene, polythiophene, and polymerized aniline. In one embodiment of the present application, the guiding agent may be polyacetylene. In another embodiment of the present application, the guiding agent may be polythiophene.
[0117] In one embodiment of the present application, in the positive electrode slurry, the mass percentage of the guiding agent is 1%-2%, which can promote the formation of a conductive network and improve the conductivity of the positive electrode sheet. Specifically, the mass percentage of the guiding agent in the positive electrode slurry can be, but is not limited to, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%. In one embodiment of the present application, the mass percentage of the guiding agent in the positive electrode slurry can be 1%-1.7%. In another embodiment of the present application, the mass percentage of the guiding agent in the positive electrode slurry can be 1.2%-2%.
[0118] In one embodiment of the present application, the solvent may be N-methylpyrrolidone.
[0119] In one embodiment of the present application, the positive electrode slurry is coated on the surface of the positive electrode current collector, and after drying, a positive electrode active material layer is formed to obtain a positive electrode sheet. Specifically, the positive electrode current collector may include but is not limited to at least one of copper, aluminum, nickel and stainless steel. In one embodiment of the present application, the positive electrode current collector may be aluminum foil.
[0120] In one embodiment of the present application, the coating method may be, but is not limited to, one of spraying, coating, roller coating, and extrusion coating. In one embodiment of the present application, the coating method may be coating. In another embodiment of the present application, the coating method may be spraying.
[0121] In one embodiment of the present application, the positive electrode active material, the guiding agent and the solvent are mixed to obtain a positive electrode slurry, and the mixing time of the positive electrode active material, the guiding agent and the solvent is 6h-10h. Specifically, the mixing time of the positive electrode active material, the guiding agent and the solvent may be, but is not limited to, 6h, 7h, 7.5h, 8h, 8.5h, 9h or 10h, etc. In one embodiment of the present application, the mixing time of the positive electrode active material, the guiding agent and the solvent may be 6h-8h. In another embodiment of the present application, the mixing time of the positive electrode active material, the guiding agent and the solvent may be 7.5h-10h.
[0122] In one embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the guiding agent and the solvent is (70-90): (10-30): (1-2): (60-70), so that the energy density of the positive electrode sheet can be increased and the polarization effect of the positive electrode sheet can be reduced. Specifically, the mass ratio of the first positive electrode material, the second positive electrode material, the guiding agent and the solvent can be, but not limited to, 70:10:1:60, 75:15:1.2:62, 75:20:1.5.9:65, 80:18:1.8:68, 85:20:1.9:69 or 90:30:2:70, etc. In one embodiment of the present application, the mass ratio of the first positive electrode material, the second positive electrode material, the guiding agent and the solvent is (70-84): (10-22): (1-1.6): (60-66). In another embodiment of the present application, the mass ratio of the first positive electrode material, the second positive electrode material, the directing agent and the solvent is (83-90):(20-30):(1.5-2):(65-70).
[0123] In one embodiment of the present application, the positive electrode slurry also includes a positive electrode conductive agent. The electron transmission capacity of the positive electrode sheet can be improved, and the conductivity of the positive electrode sheet can be improved. In one embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductive agent, the guiding agent and the solvent is (70-90): (10-30): (1.5-1.9): (1-2): (60-70), so that a positive electrode sheet with strong bonding ability, good conductivity and high energy density can be obtained. Specifically, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductive agent, the guiding agent and the solvent may be, but is not limited to, 70:30:1.5:1:60, 70:30:1.5:1.2:62, 70:20:30:1.5:1.5.9:65, 80:20:1.5:1.8:68, 85:15:1.5:1.9:69 or 90:10:1.5:2:70, etc. In one embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductive agent, the guiding agent and the solvent may be (70-85):(10-26):(1.5-1.84):(1-1.6):(60-64). In another embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductive agent, the directing agent and the solvent can be (80-90):(20-30):(1.58-1.9):(1.5-2):(63-70).
[0124] In one embodiment of the present application, the positive electrode slurry also includes a positive electrode binder. The bonding ability of the positive electrode active material can be improved, and the structural stability and mechanical properties of the positive electrode sheet can be enhanced. The mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode binder, the guide agent and the solvent is (70-90): (10-30): (2.5-3.0): (1-2): (60-70), so that a positive electrode sheet with strong bonding ability and good conductive properties can be obtained. Specifically, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode binder, the guide agent and the solvent can be, but not limited to, 70:10:2.5:1:60, 75:15:2.6:1.2:65, 75:20:2.7:1.4:65, 80:18:2.8:1.6:66, 85:20:2.9:1.8:69 or 90:30:2.9:2:70, etc. In one embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode binder, the guide agent and the solvent may be 90:10:2.9:1:30. In another embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductive agent, the positive electrode binder, the guide agent and the solvent may be 70:30:2.9:1.5:30.
[0125] In one embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductive agent, the positive electrode binder, the directing agent and the solvent is (70-90):(10-30):(1.5-1.9):(2.5-3.0):(1-2):(60-70), so that a positive electrode sheet with strong bonding ability, good conductivity and high energy density can be obtained. Specifically, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductive agent, the positive electrode binder, the guiding agent and the solvent may be, but is not limited to, 70:10:1.5:2.9:1:30, 75:15:1.6:2.9:1.2:30, 75:20:1.7:2.9:1.5:30, 80:18:1.75:2.9:1.7:30, 85:20:1.8:2.9:1.8:30 or 90:30:1.9:2.9:2:30, etc. In one embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductive agent, the positive electrode binder, the guiding agent and the solvent may be 90:10:1.5:2.9:1:30. In another embodiment of the present application, in the positive electrode slurry, the mass ratio of the first positive electrode material, the second positive electrode material, the positive electrode conductor, the positive electrode binder, the directing agent and the solvent can be 70:30:1.9:2.9:1.6:30.
[0126] The present application also provides a battery, including a negative electrode sheet and a positive electrode sheet as described in any one of the above embodiments. The battery provided by the present application has high energy density, low preparation cost, short cycle, and excellent comprehensive electrical performance, which is conducive to improving the product competitiveness of the battery.
[0127] In one embodiment of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. Specifically, the negative electrode current collector may include, but is not limited to, at least one of copper, aluminum, nickel and stainless steel. In one embodiment of the present application, the negative electrode current collector may be copper foil.
[0128] In one embodiment of the present application, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material may include but is not limited to at least one of silicon, tin, germanium, lithium and alloys thereof and carbon materials. Among them, the carbon material may include but is not limited to at least one of non-graphitized carbon, graphite, pyrolytic carbon, coke and activated carbon. In one embodiment of the present application, the negative electrode active material may be a carbon material. In another embodiment of the present application, the negative electrode active material may be a silicon material.
[0129] In one embodiment of the present application, the negative electrode active material layer also includes a negative electrode conductive agent. The negative electrode conductive agent can increase the conductivity between the active materials and improve the electronic conductivity. Specifically, the negative electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the negative electrode conductive agent may be graphite. In another embodiment of the present application, the negative electrode conductive agent may be carbon black.
[0130] In one embodiment of the present application, the negative electrode active material layer further includes a negative electrode binder, which can improve the binding ability of the components in the negative electrode active material layer and improve the binding ability between the negative electrode active material layer and the negative electrode current collector. Specifically, the negative electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the negative electrode binder can be polyvinylidene fluoride.
[0131] In one embodiment of the present application, the battery further includes a separator disposed between the positive electrode sheet and the negative electrode sheet. Specifically, the separator may be, but is not limited to, a woven membrane, a non-woven fabric, a microporous membrane, a composite membrane, a rolled membrane, or a separator paper. In one embodiment of the present application, the battery further includes an electrolyte. Among them, at least part of the positive electrode sheet and at least part of the negative electrode sheet are immersed in the electrolyte. The electrolyte of the present application is not particularly limited, and may be, but is not limited to, a substance that can be used as a battery electrolyte in the art.
[0132] The present application also provides an electrical device, which includes the battery described in any of the above embodiments. The electrical device provided in the present application has high energy density, low polarization effect, excellent comprehensive electrochemical performance, and strong market competitiveness. Electrical devices include mobile phones, tablets, watches, VR glasses, cars, etc. In one embodiment of the present application, the battery can be used in a car, which can reduce the cost of automobile electricity and increase the utilization rate of automobile electricity. In another embodiment of the present application, the battery can also be used in a mobile phone, which can increase the battery capacity of the mobile phone and improve the battery life.
[0133] The effect of the technical solution of the present application is further illustrated below through specific examples.
[0134] Example 1
[0135] The first positive electrode material source (lithium source is lithium carbonate, iron source is iron phosphate, phosphorus source is iron phosphate), the first carbon source (glucose), the first modifier (NH4Cl) and the first doping modifier (titanium dioxide) are mixed, stirred for 10 hours, and sintered at 780°C for 10 hours to obtain the first positive electrode material.
[0136] The second positive electrode material source (lithium source is lithium carbonate, iron source is iron block, phosphorus source is diammonium phosphate), the second carbon source (glucose), the second modifier (CH2CH2COOH) and the second doping modifier (titanium dioxide) are mixed, the heat treatment temperature is 100°C, the heat treatment time is 10h, after filtering and washing, sintering at 750°C for 10h to obtain the second positive electrode material.
[0137] The first positive electrode material (particle size D50 is 1.0 μm), the second positive electrode material (particle size D50 is 0.5 μm), a conductive agent (conductive carbon tube), a binder (polyvinylidene fluoride), a directing agent and a solvent (N-methylpyrrolidone) are mixed and stirred for 1 hour to obtain a positive electrode slurry, which is then applied to obtain a positive electrode sheet; the mass ratio of the first positive electrode material to the second positive electrode material is 9:1.
[0138] Example 2
[0139] The difference from Example 1 is that the mass ratio of the first positive electrode material to the second positive electrode material is 8:2.
[0140] Example 3
[0141] The difference from Example 1 is that the mass ratio of the first positive electrode material to the second positive electrode material is 7:3.
[0142] Example 4
[0143] The difference from Example 1 is that the first positive electrode material and the second positive electrode material do not include the first doping modifier and the second doping modifier.
[0144] Example 5
[0145] The difference from Example 1 is that the particle size D50 of the first positive electrode material is 0.8 μm, and the particle size D50 of the second positive electrode material is 0.3 μm.
[0146] Example 6
[0147] The difference from Example 1 is that the particle size D50 of the first positive electrode material is 1.5 μm, and the particle size D50 of the second positive electrode material is 0.1 μm.
[0148] Example 7
[0149] The difference from Example 1 is that the particle size D50 of the first positive electrode material is 1.5 μm.
[0150] Comparative Example 1
[0151] The difference from Example 1 is that the particle size D50 of the second positive electrode material is 1 μm.
[0152] Comparative Example 2
[0153] The difference from Example 1 is that the first modifier and the second modifier are not added during the preparation of the first positive electrode material and the second positive electrode material.
[0154] Comparative Example 3
[0155] The difference from Example 1 is that the first modifier and the second modifier are the same modifier, and the first group and the second group are the same group.
[0156] Comparative Example 4
[0157] The difference from Example 1 is that the positive electrode slurry does not include a directing agent.
[0158] Performance Testing
[0159] The positive electrode sheets prepared in the above-mentioned Examples 1-7 and Comparative Examples 1-4 were subjected to a compaction density test, and the test conditions were: rolling under the maximum pressure of the roller press, measuring the thickness of the positive electrode sheet after rolling, and calculating the compaction density by the following formula: Compaction density = positive electrode sheet surface density / (positive electrode sheet thickness - positive electrode current collector thickness), and the results are shown in Table 1.
[0160] The positive electrode plates and negative electrode plates (graphite) prepared in the above-mentioned Examples 1-7 and Comparative Examples 1-4 and the electrolyte (including 1.0 mol of lithium hexafluorophosphate (LLiPF6), ethylene carbonate (EC), dimethyl carbonate (DMC), vinylene carbonate (VC) and fluoroethylene carbonate (FEC)) were assembled, formed and divided to prepare a battery. The prepared battery was subjected to an impedance (DCIR) test under the following test conditions: the battery was tested using a Macro test cabinet, and the battery was charged and discharged for 30 seconds at a current density of 0.5C under 100% SOC conditions, and the standing time between charge and discharge was 30 minutes. The charge and discharge impedance (DCIR) of the battery was tested, and the results are shown in Table 2.
[0161] The positive electrode sheets and negative electrode sheets (graphite) and electrolyte (including 1.0 mol of lithium hexafluorophosphate (LLiPF6), ethylene carbonate (EC), dimethyl carbonate (DMC), vinylene carbonate (VC) and fluoroethylene carbonate (FEC), prepared in a mass percentage of 16:50:30:3:1) prepared in the above-mentioned Examples 1-7 and Comparative Examples 1-4 were assembled, formed, and divided into volumes to prepare batteries for energy efficiency testing. The test conditions were: using a Ruineng test cabinet for testing, the battery was charged and discharged for 100 cycles under the voltage range of 2.0-3.8V and 0.5CP constant power conditions, and the ratio of discharge energy to charging energy was calculated. Two batteries were tested for each test, and the average value was taken to obtain the energy efficiency of the battery. The results are shown in Table 2.
[0162] Table 1 Performance test results of positive electrode
[0163] <![CDATA[Compaction density (g / cm 3 )]]> Example 1 2.67 Example 2 2.65 Example 3 2.62 Example 4 2.61 Example 5 2.64 Example 6 2.68 Example 7 2.69 Comparative Example 1 2.50 Comparative Example 2 2.49 Comparative Example 3 2.55 Comparative Example 4 2.60
[0164] Table 2 Battery performance test results
[0165] 0.5C charging impedance (Ω) 0.5C discharge impedance (Ω) Energy efficiency (%) Example 1 0.00728 0.00569 93.76 Example 2 0.00699 0.00556 93.94 Example 3 0.0069 0.00549 94.125 Example 4 0.0076 0.0071 90.9 Example 5 0.0073 0.0057 93 Example 6 0.0075 0.007 91.2 Example 7 0.0074 0.0066 91.5 Comparative Example 1 0.00765 0.0073 90.8 Comparative Example 2 0.00773 0.00786 90.7 Comparative Example 3 0.0078 0.0072 90.5 Comparative Example 4 0.009 0.008 90
[0166] According to Examples 1-7 and Comparative Examples 1-4, it can be seen that the first group and the second group on the surface of the first positive electrode material and the second positive electrode material can enhance the mixing uniformity and conductivity of the positive electrode active material, and improve the compaction density and energy efficiency of the positive electrode sheet. According to Examples 1-3, it can be seen that the appropriate mass ratio of the first positive electrode material and the second positive electrode material can further improve the compaction density and energy efficiency of the positive electrode sheet. According to Examples 5-7 and Comparative Example 1, it can be seen that the appropriate particle size of the first positive electrode material and the second positive electrode material and the particle size of the first positive electrode material are greater than the particle size of the second positive electrode material, which can reduce the impedance of the positive electrode sheet and improve the compaction density and energy efficiency of the positive electrode sheet. According to Example 1 and Comparative Examples 2-3, it can be seen that the first group and the second group on the surface of the first positive electrode material and the second positive electrode material can form a conductive network and enhance the electrochemical performance of the positive electrode sheet. The selection of the appropriate first group and the second group can further enhance the uniform distribution of the positive electrode active material and improve the compaction density and energy efficiency of the positive electrode sheet. It can be seen from Example 1 and Comparative Example 4 that the directing agent can connect the first group and the second group, increase the conductive path of the positive electrode active material, and further improve the energy efficiency of the positive electrode sheet. Therefore, the present application provides a positive electrode active material with good mixing uniformity between different particle sizes.
[0167] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material includes a first positive electrode material and a second positive electrode material, the surface of the first positive electrode material has a first group, the surface of the second positive electrode material has a second group, the first group and the second group are independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group can be bonded and connected, and the particle size of the first positive electrode material is larger than the particle size of the second positive electrode material.
2. The positive electrode active material according to claim 1, characterized in that The first group and the second group can be connected by hydrogen bonding and / or chemical bonding.
3. The positive electrode active material according to claim 1, characterized in that The particle size D50 of the first positive electrode material is 0.8 μm-1.5 μm, and the particle size D50 of the second positive electrode material is less than or equal to 0.5 μm.
4. The positive electrode active material according to claim 1, characterized in that The mass ratio of the first positive electrode material to the second positive electrode material is (9-7):(3-1).
5. The positive electrode active material according to claim 1, characterized in that The first positive electrode material includes a first core and a first carbon coating layer disposed on the surface of the first core, and the first carbon coating layer has a first group; In the first positive electrode material, the mass percentage of the first carbon coating layer is 1.1%-1.3%; The second positive electrode material includes a second core and a second carbon coating layer disposed on the surface of the second core, and the second carbon coating layer has a second group; In the second positive electrode material, the mass percentage of the second carbon coating layer is 1.1%-1.3%.
6. The positive electrode active material according to claim 5, characterized in that The materials of the first core and the second core are independently selected from at least one of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate and ternary materials.
7. A method for preparing a positive electrode active material, characterized in that: include: Mixing a first cathode material source and a first modifier to form a first mixture, and performing a first sintering to obtain a first cathode material; Mixing a second positive electrode material source and a second modifier to form a second mixture, and performing a second sintering to obtain a second positive electrode material; The first positive electrode material and the second positive electrode material are mixed to obtain a positive electrode active material; the positive electrode active material includes the first positive electrode material and the second positive electrode material, the surface of the first positive electrode material has a first group, the surface of the second positive electrode material has a second group, the first group and the second group are independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group can be bonded and connected, and the particle size of the first positive electrode material is larger than the particle size of the second positive electrode material.
8. The preparation method according to claim 7, characterized in that: The first modifier and the second modifier are independently selected from CH2CH2COOH, CH2CH2CH2COOH, NH4Cl, (NH4)2SO4, NH4NO3, Na2SO4, H2SO4, CH3C4H4O 2、 At least one of C4H4O2, NH3H2O and CH3COOH.
9. The preparation method according to claim 7, characterized in that: The first mixture further includes a first carbon source, and the second mixture further includes a second carbon source, wherein the first carbon source and the second carbon source are independently selected from at least one of glucose, sucrose, citric acid, polyethylene glycol, carbon nanotubes and graphene.
10. The preparation method according to claim 9, characterized in that: The mass ratio of the first cathode material source, the first modifier and the first carbon source is (2.52-2.58):(0.0038-0.0047):(6.5-6.7); The mass ratio of the second positive electrode material source, the second modifier and the second carbon source is (2.52-2.58):(0.0012-0.0025):(5.1-5.5).
11. The preparation method according to claim 7, characterized in that: The temperature of the first sintering is 750° C.-800° C., and the time of the first sintering is 15 h-20 h; The temperature of the second sintering is 700° C.-800° C., and the time of the second sintering is 3 h-7 h.
12. A composite positive electrode material, characterized in that: The composite active material includes a first positive electrode material and a second positive electrode material, the surface of the first positive electrode material has a first group, the surface of the second positive electrode material has a second group, the first group and the second group are independently selected from at least one of -NH2, -C4H4O2, -COOH and -S, the first group and the second group are connected by a connecting group, and the particle size of the first positive electrode material is larger than the particle size of the second positive electrode material.
13. The composite positive electrode material according to claim 12, characterized in that The first group, the connecting group and the second matrix are connected by hydrogen bonds and / or chemical bonds.
14. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode active material layer, and the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 6, or the positive electrode active material prepared by the preparation method according to any one of claims 7 to 11, or the composite positive electrode material according to any one of claims 12 to 13.
15. The positive electrode sheet according to claim 14, characterized in that: The compaction density of the positive electrode sheet is 2.6 g / cm 3 -2.7g / cm 3 .
16. A method for preparing a positive electrode sheet, characterized in that: include: Mixing the positive electrode active material according to any one of claims 1 to 6 or the positive electrode active material prepared by the preparation method according to any one of claims 7 to 11, a directing agent and a solvent to obtain a positive electrode slurry; The positive electrode slurry is coated and dried to obtain a positive electrode sheet.
17. The preparation method according to claim 16, characterized in that: In the positive electrode slurry, the mass percentage of the directing agent is 1%-2%; The directing agent includes at least one of an iron-based polymer phthalocyanine compound, polyacetylene, polythiophene and polymerized aniline.
18. A battery, characterized in that: The battery comprises a negative electrode sheet and a positive electrode sheet as described in any one of claims 14-15 or a positive electrode sheet prepared by the preparation method as described in any one of claims 16-17.
19. An electrical equipment, characterized in that: The electrical device comprises the battery according to claim 18.